Decision Making in a Hybrid Organization: A Case Study of a Southwestern Drug Court Treatment Program. Issue 1 (22nd March 2012) - Baker, Kimberly M.
<x xml:space="preserve">Abstract</x> This article presents a case study of decision making in a drug court located the southwestern United States. This study seeks to fill a gap in research on decision making by attending to the ways that drug court officials navigate the demands of a court that is dedicated to both therapy and criminal justice. This analysis differs from previous research by viewing the drug court as a "hybrid organization" and asking how the staff members interact in the decision‐making process. Additionally, this research provides an opportunity to investigate the concerns over collaborative decision making raised by critics. The data from this case study reveal that as a hybrid organization, the drug court staff often divides along institutional lines by allowing the counseling staff to manage treatment and the judge to manage punishment. When tensions arise, they are resolved by the structure of the court, which is hierarchical rather than collaborative.